Fabrication and characterization of zein-encapsulated Litsea cubeba oil nanoparticles and its effect on the quality of fresh pork. (October 2022) - Xia, Yuting; Wang, Yan; Lou, Shangrong; Wen, Mengting; Ni, Xuewen
Abstract: This study aims to fabricate and characterize zein-encapsulated Litsea cubeba oil nanoparticles (NZ/LCO) and evaluate its effect on pork preservation. The formation, morphology, interactions, thermal stability, antibacterial and antioxidant properties and in vitro release of NZ/LCO were investigated. NZ/LCO showed a spherical shape with a smooth outer wall under scanning electron microscope. Fourier-transform infrared spectroscopy revealed that there were hydrogen bonding interactions between Litsea cubeba oil (LCO) and zein. The glass transition temperature of NZ/LCO was higher than that of zein nanoparticles by differential scanning calorimetry. Encapsulation of LCO in zein improved antibacterial and antioxidant activities of LCO. The antibacterial effect of NZ/LCO against Staphylococcus aureus was stronger than that against Escherichia coli . NZ/LCO exhibited sustained and pH-dependent release of LCO in vitro, and the release was faster in pH 4.5 buffer than in pH 7 buffer. When the ratio of zein to LCO was 1:0.5, the particle size and polydispersity index of NZ/LCO were 128.3 nm and 0.148, respectively, and its performance was the best. Compared with the coating containing free LCO, the coating containing NZ/LCO had better preservation effect on pork because it better delayed the changes in color, pH and texture of pork, and inhibited lipid oxidation and microbial growth more effectively. The findings suggest that NZ/LCO has a high potential for pork preservation.